Distribuição natural de espécies arbóreas em áreas com diferentes níveis de antropização e relação com os atributos químicos do solo - Calgaro, Hemerson Fernandes; Buzetti, Salatier [UNESP]; Silva, Letcia Rodrigues [UNESP]; Stefanini, Lorraine [UNESP]; Montenegro de Miranda, Luiz Paulo [UNESP]; Moraes, Marcela Aparecida de [UNESP]; Teixeira de Moraes, Mario Luis [UNESP] (Univ Federal Vicosa, 2015)
With the emergence of areas degraded by human activities, the chemical soil properties and silvicultural characters became important in understanding the succession process of tree species and planning of landscape restoration. This study aimed to evaluate the distribution of tree species in areas with different levels of human disturbance, relating silvicultural aspects to the soil chemical properties and characterizing the type of vegetation, for integration of genetic conservation program in situ. The study was conducted in the area of Research and Extension Experimental Farm (FEPE) from UNESP, Ilha Solteira, in Selviria - MS. Through transect, 64 plots were marked 50 m equidistant with dimensions of 10 x 10 m, where: 29 plots were in an highly disturbed area (HDA), five in moderately disturbed area (MDA), 15 in lowly disturbed area (LDA), six in riparian stream of Vestia river (Riparian Forest) and nine in the legal reserve. Soil samples were collected at two depths (0.0 to 0.20 and 0.20 to 0.40 m) for the chemical analysis and the assessment of silvicultural characters, such as height, diameter at breast height (DBH) and shape. The study of the natural distribution of tree species and edaphic condition in the different evaluated areas showed that: the soil chemical properties associated with the level of human disturbance and conservation of the areas are influencing the natural occurrence, species diversity and development of the trees. Height, DBH and shape are good indicators to assess the growth of the tree community and relate them to soil chemical properties; LDA and legal reserve presented higher natural occurrence, number of individuals and number of species. In the riparian forest, basal area values, height, shape and chemical soil properties were higher. From the 97 species found, six have the potential to be used in a program of genetic conservation in situ. They are: Astronium fraxinifolium, Terminalia argentea, Curatella americana, Cupania vernalis, Qualea jundiahy and Andira cuyabensis.

Com o surgimento de áreas degradadas por ações antrópicas, os atributos químicos do solo e os caracteres silviculturais passaram a ter importância quanto ao entendimento do processo sucessional das espécies arbóreas e ao planejamento de recomposição da paisagem. Assim, este trabalho teve como objetivo avaliar a distribuição de espécies arbóreas em áreas com diferentes níveis de antropização, relacionando aspectos silviculturais com os atributos químicos do solo e caracterizando o tipo de vegetação, para fins de integração de programa de conservação genética in situ. O trabalho foi desenvolvido em área da Fazenda Experimental de Pesquisa e Extensão (FEPE) da UNESP, de Ilha Solteira, no Município de Selvíria, MS. Por meio de transecto, foram demarcadas 64 parcelas equidistantes de 50 m com dimensões de 10 x 10 m, sendo 29 parcelas em área altamente antropizada (AAA), cinco em área medianamente antropizada (AMA), 15 em área pouco antropizada (APA), seis na Mata Ciliar do córrego da Véstia (Mata Ciliar) e nove na Reserva Legal. As amostras de solo foram coletadas em duas profundidades (0,0 a 0,20 m e 0,20 a 0,40 m) para os atributos químicos, além da avaliação dos caracteres silviculturais, como altura, Diâmetro à Altura do Peito (DAP) e Forma. O estudo da distribuição natural de espécies arbóreas e condição edáfica nas diferentes áreas avaliadas permitiu concluir que os atributos químicos do solo, associados ao nível de antropização e conservação das áreas, estão influenciando a ocorrência natural, diversidade de espécies e desenvolvimento dos indivíduos arbóreos. A altura, DAP e Forma são bons indicadores para avaliar o crescimento da comunidade arbórea e relacioná-los aos atributos químicos do solo. A APA e a Reserva Legal apresentam maior ocorrência natural, número de indivíduos e número de espécies. Na Mata Ciliar, os valores de área basal, altura, forma e atributos químicos do solo foram superiores. Das 97 espécies encontradas, seis têm potencial para serem utilizadas num programa de conservação genética in situ. São elas: Astronium fraxinifolium, Terminalia argentea, Curatella americana, Cupania vernalis, Qualea jundiahy e Andira cuyabensis.
Natural distribution of tree species in areas with different levels of human disturbance and its relation with chemical properties of the soil
Keywords: Cerrado; Soil fertility; Degraded area